Studi Analisis Kecemasan pada Remaja Putri dengan Obesitas di Kabupaten Semarang: Anxiety Analysis Study in Obese Adolescent Girls in Semarang Regency - Trimawati; Mona Saparwati; Abdul Wahid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2026)
Adolescent obesity is a growing public health problem worldwide and is associated not only with physical health consequences but also with mental health problems, particularly anxiety. Adolescent girls are more vulnerable to anxiety due to social and cultural pressures related to body image. This study aimed to examine the relationship between nutritional status based on body mass index (BMI) and anxiety levels among adolescent girls. This study employed a quantitative cross-sectional design. A total of 155 adolescent girls aged 15–18 years from SMAN 1 Bergas and SMAN 1 Tuntang were selected using proportional sampling. Nutritional status was assessed by measuring body weight and height to calculate BMI, while anxiety levels were measured using the Generalized Anxiety Disorder (GAD) questionnaire. Data were analyzed using univariate and bivariate analyses, including Fisher’s Exact test. Most participants had normal nutritional status (58.7%), while 10.3% were overweight and 1.9% were classified as obese. The most common anxiety level was mild anxiety (37.4%), followed by moderate (26.5%) and severe anxiety (10.3%). Bivariate analysis revealed a significant association between nutritional status and anxiety levels (p < 0.001), with a clear trend of increasing anxiety severity as nutritional status progressed from normal to overweight and obesity. Nutritional status, particularly overweight and obesity, is significantly associated with higher anxiety levels among adolescent girls. These findings highlight the importance of integrated interventions addressing both obesity prevention and mental health promotion in adolescent populations. ABSTRAK Obesitas pada remaja merupakan masalah kesehatan masyarakat yang semakin meningkat dan tidak hanya berdampak pada kesehatan fisik, tetapi juga pada kesehatan mental, khususnya kecemasan. Remaja putri merupakan kelompok yang lebih rentan mengalami kecemasan akibat tekanan sosial terkait citra tubuh. Penelitian ini bertujuan untuk menganalisis hubungan antara status gizi berdasarkan indeks massa tubuh (IMT) dengan tingkat kecemasan pada remaja putri. Penelitian ini menggunakan desain kuantitatif dengan pendekatan cross-sectional. Subjek penelitian adalah 155 remaja putri usia 15–18 tahun yang bersekolah di SMAN 1 Bergas dan SMAN 1 Tuntang, yang dipilih menggunakan teknik proportional sampling. Status gizi diukur melalui pengukuran berat badan dan tinggi badan untuk menghitung IMT, sedangkan tingkat kecemasan diukur menggunakan kuesioner Generalized Anxiety Disorder (GAD). Analisis data dilakukan menggunakan uji univariat dan bivariat dengan uji Fisher Exact. Mayoritas responden memiliki status gizi normal (58,7%), namun ditemukan 10,3% gizi lebih dan 1,9% obesitas. Tingkat kecemasan terbanyak berada pada kategori cemas ringan (37,4%), diikuti cemas sedang (26,5%) dan cemas berat (10,3%). Analisis bivariat menunjukkan terdapat hubungan yang signifikan antara status gizi dengan tingkat kecemasan (p < 0,001), dengan kecenderungan peningkatan tingkat kecemasan seiring meningkatnya status gizi dari normal menuju gizi lebih dan obesitas. Status gizi, khususnya gizi lebih dan obesitas, berhubungan signifikan dengan peningkatan tingkat kecemasan pada remaja putri. Temuan ini menegaskan pentingnya pendekatan holistik yang mengintegrasikan intervensi pengendalian obesitas dan dukungan kesehatan mental pada remaja putri.